New architectural design of delivery room reduces morbidity in preterm neonates: a prospective cohort study - Terrin, Gianluca; Conte, Francesca; Scipione, Antonella; Aleandri, Vincenzo; Di Chiara, Maria; Bacchio, Erica; Messina, Francesco; De Curtis, Mario (BMC pregnancy and childbirth, 2016)
Background A multidisciplinary committee composed of a panel of experts, including a member of the American Academy of Pediatrics and American Institute of Architects, has suggested that the delivery room (DR) and the neonatal intensive care units (NICU) room should be directly interconnected. We aimed to investigate the impact of the architectural design of the DR and the NICU on neonatal outcome. Methods Two cohorts of preterm neonates born at < 32 weeks of gestational age, consecutively observed during 2 years, were compared prospectively before (Cohort 1: “conventional DR”) and after architectural renovation of the DR realized in accordance with specific standards (Cohort 2: “new concept of DR”). In Cohort 1, neonates were initially cared for a conventional resuscitation area, situated in the DR, and then transferred to the NICU, located on a separate floor of the same hospital. In Cohort 2 neonates were assisted at birth directly in the NICU room, which was directly connected to the DR via a pass-through door. The primary outcome of the study was morbidity, defined by the proportion of neonates with at least one complication of prematurity (i.e., late-onset sepsis, patent ductus arteriosus, intraventricular hemorrhage, periventricular leukomalacia, bronchopulmonary dysplasia, retinopathy of prematurity and necrotizing enterocolitis). Secondary outcomes were mortality and duration of hospitalization. Statistical analysis was performed using standard methods by SPSS software. Results We enrolled 106 neonates (56 in Cohort 1 and 50 in Cohort 2). The main clinical and demographic characteristics of the 2cohorts were similar. Moderate hypothermia (body temperature ≤ 35.9 ° C) was more frequent in Cohort 1 (57 %) compared with Cohort 2 (24 %, p = 0.001). Morbidity was increased in Cohort 1 (73 %) compared with Cohort 2 (44 %, p = 0.002). No statistically significant differences in mortality and median duration of hospitalization were observed between the 2 cohorts of the study. Conclusions If realized according to the proposed architectural standards, renovation of DR and NICU may represent an opportunity to reduce morbidity in preterm neonates.